Orofacial Lymphedema in Phelan–McDermid Syndrome: A Case of Hemifacial Involvement and a Scoping Review - Domenico De Falco; Dario Di Stasio; Dorina Lauritano; Alberta Lucchese; Massimo Petruzzi (Applied Sciences, 2025)
Phelan–McDermid syndrome (PMS) is a rare genetic disorder primarily caused by deletions or structural alterations of chromosome 22q13, often involving the SHANK3 gene. However, mutations in other genes, such as CELSR1, or deletions in the interstitial regions of 22q13 contribute to the phenotypic variability of PMS. The syndrome is characterized by developmental delay, cognitive impairment, absent or significant impairment speech, autism spectrum disorder (ASD), and distinctive craniofacial features. Lymphedema, present in 10–25% of cases, typically affects peripheral regions, while facial involvement has not been documented to date. Orofacial manifestations frequently include dolichocephaly, widely spaced eyes, prominent ears, and dysmorphic features, such as a bulbous nose and arched palate. This scoping review analyzed seven studies on orofacial features associated with PMS, highlighting a higher phenotypic variability, with frequent findings of intellectual disability, hypotonia, and craniofacial dysmorphisms. Genomic analyses identified consistent deletions in 22q13.31–q13.33 and complex genomic rearrangements. This review, through the report of the first documented case of hemifacial lymphedema in the literature, analyzes the facial features of patients with PMS and their genetic origins. It also highlights the importance of interdisciplinary collaboration and inclusive genetic testing to better define the phenotypic spectrum of this syndrome. A deeper understanding of the genetic and clinical characteristics of PMS can facilitate early diagnosis and personalized management for these patients.